The Current And The Future Scenario Of The Industrial Sector In Saida City: A Statistical Study (Journal of Economics and Management Research, 2020)
The aim of this paper is to study the impact of the contribution of both public and private sectors of the State and the private sector, as well as small and medium enterprises in the development of the industrial sector, especially the manufacturing industry in Saida city by conducting an analytical, statistical study from 2011-2018 for the number of public and private small and medium enterprises active in the industrial sector, The study concluded that there was a significant contribution to the private sector in the development of this vital sector, but despite the incentives provided by the local authorities, this sector did not rise to the required level due to the lack of funding, investment rule 49-51, and poor governance by local authorities.